Characterization of mefenamic acid ester produrgs : physicochemical properties transepithelial and efflux across Caco-2 Cell Monolayers - Kamonthip Wiwattanawongsa (Prince of Songkla University, 2005)
Thesis ( Ph.D., Pharmaceutical Science)--Prince of Songkla University, 2005